2021
DOI: 10.2196/30529
|View full text |Cite
|
Sign up to set email alerts
|

Mild Adverse Events of Sputnik V Vaccine in Russia: Social Media Content Analysis of Telegram via Deep Learning

Abstract: Background There is a limited amount of data on the safety profile of the COVID-19 vector vaccine Gam-COVID-Vac (Sputnik V). Previous infodemiology studies showed that social media discourse could be analyzed to assess the most concerning adverse events (AE) caused by drugs. Objective We aimed to investigate mild AEs of Sputnik V based on a participatory trial conducted on Telegram in the Russian language. We compared AEs extracted from Telegram with ot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 55 publications
(51 reference statements)
4
15
1
1
Order By: Relevance
“…Initially, countries like Peru, temporarily suspended the trials of Covid vaccine after finding neurological problems in one volunteer [15]. Furthermore, studies conducted in countries like Canada and Russia reported symptoms more among the female population than in male which is in contrast to the findings of our study [16,17].…”
Section: Discussioncontrasting
confidence: 89%
“…Initially, countries like Peru, temporarily suspended the trials of Covid vaccine after finding neurological problems in one volunteer [15]. Furthermore, studies conducted in countries like Canada and Russia reported symptoms more among the female population than in male which is in contrast to the findings of our study [16,17].…”
Section: Discussioncontrasting
confidence: 89%
“…Our models showed a higher risk for women and young people to experience AEs. A real-world study that reported AEFI of patients receiving BNT162b2 mRNA, mRNA-1273, or Ad26COV2 in one or two doses ( 35 ), an independent studies conducted with Gam-COVID also confirmed this result ( 33 , 36 ). The study of Ramasamy et al.…”
Section: Discussionmentioning
confidence: 70%
“…For most patients, at least one AEFI occurred with all types of vaccines during the first 24 hrs. after injection, and most of them qualified the symptoms as "very mild" or "mild" both after the first and second dose, except for mRNA-1273 for which nearly half of the volunteers reported moderate symptoms after the second dose as reported previously (18,20,(22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 51%
“…Our models showed a higher risk for women and young people to experience AEs. A real-world study that reported AEFI of patients receiving BNT162b2 mRNA, mRNA-1273, or Ad26COV2 in one or two doses (28) , an independent studies conducted with Gam-COVID also confirmed this results (26,29). The study of Ramasamy et al on ChAdOx1 showed more adverse events in the group of 18-55 years old (22).…”
Section: Discussionmentioning
confidence: 70%